Denmark : Financial Sector Assessment Program-Technical Note-Systemic Liquidity. (IMF Staff Country Reports; Country Report ;, 2020)
The functioning of money markets, FX swaps markets and in particular covered bond markets are crucial for the Danish financial system. Liquidity conditions in the Danish financial sector are affected by central bank operations and the lending and funding activities of financial institutions. Nearly 100 percent of the mortgage funding is obtained from market sources, using mainly domestically issued covered bonds. Correspondingly, money markets and foreign exchange (FX) swap markets are crucial to the credit intermediation process and a dislocation in these markets-the inability of financial institutions to roll over or obtain new funding or hedging positions-may have significant consequences for financial stability. Against this background, this note analyzes core funding markets for Danish banks and assesses Danmarks Nationalbank's (DN's) capacity to manage systemic liquidity conditions in normal times and in times of stress.